PENDAPATAN ASLI DAERAH PROVINSI SUMATERA SELATAN: DARI KONTRIBUSI RETRIBUSI PASAR - Rita Martini (Universitas Cenderawasih, 2019)
AbstractThis study aims to analyze the effect of market retribution contributions on Regional Original Revenue (PAD). This type of research is associative descriptive with quantitative methods. The study was conducted on twelve districts/cities in South Sumatra Province. The data used in the form of financial statements of the local government of South Sumatra Province during the 2014-2016 period from the Republic of Indonesia Supreme Audit Agency (BPK RI). The analysis technique uses the Simple Linear Regression method. This stud y proves that the contribution of market retribution is 19.30% of the PAD of regencies/cities in the province of South Sumatra, which are classified as very low. The low contribution of market retribution to PAD is the duty of the government to explore the potential that can be used as a source of revenue for regional retribution. Keywords: local revenue, market retribution